(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2026)
Rapid urbanization processes and the continuous growth of urban population are causing an increasing pressure on urban systems and services worldwide. Ensuring efficient, accessible, and environmentally friendly urban services has become a pivotal precondition towards maintaining a relevant life quality and achieving sustainable cities. The system of urban services (including transportation, utilities, housing, waste management, etc.) plays a central role in supporting economic efficiency, social equity and environmental balance. In this context, sustainability requires a balanced approach integrating environmental protection, economic efficiency, social inclusion and effective governance. Meanwhile, urban areas face a number of interconnected challenges: environmental pollution, aging infrastructure, unequal access to services, weak institutional coordination, etc. Addressing these issues requires integrated planning, smart technologies, as well as inclusive and long-term policymaking frameworks. This paper studies the process of sustainable development of urban services, analyzing their theoretical and conceptual framework, key sustainability principles and the main challenges. It also examines the existing issues and best practices on the case of Yerevan, highlighting both problems and ongoing initiatives towards ensuring sustainable urban services.